Hydroelectric energy renewable energy and the environment - Pandey, Bikash; Karki, Ajoy (Energy and the environment, 2017)
The authors demonstrate an in-depth technical know-how on hydropower systems based on decades of field experience. The subject covers both the technical theory and the practical know-how on how to design and implement small hydropower projects from A to Z.